Habilidades de pre cálculo en estudiantes de primer grado de cuatro instituciones educativas del Callao - Bobadilla Cornelio, Juana (2012)
The research aimed to determine the level of development of the skills of pre calculation from first graders four schools of Callao, as with the pre test calculation Milicic and Schmidt and adapted by Drain, Delgado and Carpio (2005) . We used simple descriptive design. The sample consisted of 173 students in first grade. The results showed that pre calculation skills in first graders are at an average level of development. Skills: Basic concepts, visual perception, ordinal numbers and figures playback observe a medium level of development while skills: matching term by term, recognition of geometric figures, number recognition and reproduction, cardinality, and arithmetic problem solving conservation observed low level of development. No gender differences were found.